IDENTITĂŢI LITERARE - 2011 (II) - RUSU, Nicolae (BIBLIOPOLIS, 2020)
This is a critical presentation of the recent successfull work of the Roumanian writers from Chisinau through the prism of demands oftheJury of Moldova Writers Union. The au-thor analyse carefull the literary production of the 2011, by categories which coincide with the literary genres: children books, prose, po-etry, essays, memoirs etc. Thus the librarians and readers have at hand a guide of authors worth reading.